1984
DOI: 10.1177/028418518402500208
|View full text |Cite
|
Sign up to set email alerts
|

Cranio-Caudal Movements of the Liver, Pancreas and Kidneys in Respiration

Abstract: The range of movement of the liver, pancreas and kidneys in maximum and normal respiration, and the ability to suspend respiration repeatedly leaving the organs in exactly the same position with the aid of given instructions or a combination of instructions and a simple tool were investigated. The range of movement of the most mobile organ (liver) was 5.5 cm during maximum, 2.5 cm during normal, 0.9 cm during suspended respiration, and 0.2 cm during suspended respiration with a bar placed above the abdomen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
150
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(158 citation statements)
references
References 7 publications
(1 reference statement)
7
150
0
Order By: Relevance
“…Respiration-induced craniocaudal, lateral, and anteroposterior motions have been observed (1). Motion in the craniocaudal direction is the most significant of the three, with translations of the liver ranging from 10 to 26 mm during quiet respiration and larger translations, as much as 55-60 mm, seen during deep respiration (1,4). In addition, Shirato et al (5) reported anteroposterior motions ranging from 4 to 8 mm, along with motions of 5-9 mm in the lateral axis.…”
Section: Discussionmentioning
confidence: 99%
“…Respiration-induced craniocaudal, lateral, and anteroposterior motions have been observed (1). Motion in the craniocaudal direction is the most significant of the three, with translations of the liver ranging from 10 to 26 mm during quiet respiration and larger translations, as much as 55-60 mm, seen during deep respiration (1,4). In addition, Shirato et al (5) reported anteroposterior motions ranging from 4 to 8 mm, along with motions of 5-9 mm in the lateral axis.…”
Section: Discussionmentioning
confidence: 99%
“…The liver motion is more complicated, as it is the most movable abdominal organ (Suramo et al, 1983), and does not have a fixed relationship to the skin surface or the surrounding organs (Clifford et al, 2002;Siva et al, 2013), although they are related by ligaments or membranes (O'Rahilly and Müller, 1983). Thus, the liver can be subject to both sliding and free discontinuous motion ( Fig.…”
Section: D Ct Liver Images Datasetmentioning
confidence: 99%
“…Eight publications where found describing kidney motion under deep breathing (19)(20)(21)(22) or from breath hold instructions (21,(23)(24)(25)(26). No external devices were used on the abdomen.…”
Section: Kidney Motion During Deep Breathing/breath Holdmentioning
confidence: 99%